SEISMICITY AND GPS CONSTRAINTS ON CRUSTAL DEFORMATION IN THE SOUTHERN PART OF THE KOREAN PENINSULA - Jin S.; Park P.-H.; Li Z.C. (My University, 2006)
Three years of continuous observations at 45 GPS sites in South Korea show horizontal deformation velocities are less than 3 mm/yr with respect to the stable South Korea block. These velocities and the associated horizontal strain rate reveal that South Korea is dominated by both ENE-WSW compression and NNW-SSE extension. Compared to the seismic strain rate in South Korea derived from recently recorded earthquake data (Mw > 4.0, 1936-2004), the principal horizontal axes of both strain rate tensors are nearly consistent, indicating that the seismicity can be used to improve GPS-derived deformation style and orientation. In addition, it also reflects that the occurrence of shallow earthquakes in South Korea is closely related with the horizontal strain.
Keywords: CRUSTAL DEFORMATION; GPS; KOREAN PENINSULA; SEISMICITY; STRAIN RATE